SYNTHESIS AND STRUCTURAL CHARACTERIZATION nanocopper ( o) VIA MICROWAVE - ULTRASOUND , STABILIZED WITH TYPE OLIGOMERS TEREPHTHALATE BIS -2 - hydroxyethyl ( BHET ) - Guzmán Duxtan, A. (2013)
This paper describes the synthesis and characterization of copper nanoparticles (O) - Cu NPs (O) - applying the method assisted polyol ( glycolysis ) microwave ( MW ) , using an organic synthetic precursor of Cu ( II ) previously synthesized and polyethylene terephthalate ( PET ), the depolymerization reaction by MW was conducted with ethylene glycol (EG) by its high dielectric constant ( 41.4 at 298K ) and dielectric loss , allowing it to be rapidly heated with microwave radiation and achieving speed reduction rate metal ions in the system. At this stage , the formed byproducts are terephthalate , bis ( 2-hydroxyethyl ) ( BHET ) , dimers of BHET and / or oligomers thereof, which serve as stabilizing agents and to achieve encapsulate NPsCu (O) , preventing their autoxidation . Subsequently, the system was subjected to an ultrasonic pulse ( U.S. ) , which due to the internal cavilación generates high pressures and temperatures in the grain boundary edge , enabling disintegration of the nanometric particles . Furthermore, simultaneous testing was performed by varying the precursor to the same reaction conditions , also the synthesis of NPsCu (O) was assayed using a commercial plasticizer phthalate, di -octyl phthalate (DOP ) used in the line PVC process for evaluating the stability of the nanoparticles in such products. Structural characterization of the NPsCu (O) was made by XRD and surface phenomena study were evaluated by UV-VIS spectrophotometry . PET and identification was performed by FTIR BHET